Implementation Of Competency Improvement Policy For Job Seekers By The North Central Timor Regency Manpower And Transmigration Office - Legan, Eugenius Yogeputra; Fritantus, Yohanes; Rembu, Yoakim (Public Policy Journal, 2025)
The purpose of this study is to describe how "the implementation of competency improvement for job seekers by the Manpower and Transmigration Office of North Central Timor Regency". This study uses descriptive research with a qualitative approach. The data analysis techniques used are data collection, data reduction, data presentation, and conclusions drawn. Based on the results of the competency improvement training research for job seekers, it shows that TTU Regency has implemented a competency improvement training program for job seekers quite well. Starting from the management of the organizational structure, clear division of duties and functions in each unit in the organization, especially the units that run the training program, the source of funds for the implementation of the competency improvement training program comes from (APBN) and (APBD), the TTU Regency Directorate also conducts educational methods to the community through social media and brochures, competency improvement training for job seekers is programmed once a year with the method of presenting material offline and organizational practices are structurally carried out by the field of training and placement of Workers and are carried out at the Job Training Center (BLK) of TTU Regency.